Elektronizace veřejné správy jako nástroj omezování korupce - Linhartová, Veronika; Tvrdíková, Veronika (Univerzita Pardubice, 2019)
The paper deals with the influence of electronization on the reduction of corruption in public administration. According to a number of studies, corruption in public administration has an impact on a wide range of taxpayers. They may feel the consequences of corrupt behaviour, for example in the form of tax and price increases or poor quality of service. For this reason, corruption is considered one of the most serious problems as it affects a large part of society. A number of empirical studies have shown that one of the ways to limit corruption is the electronization of public administration. For analysis, a group of 113 countries from all over the world were used, regardless of their geographical jurisdiction or political establishment. The time period is from 2003 to 2017. In order to fulfil the goal, the graphical interpretation of Bag plots and linear regression analysis is used to assess the impact of selected variables on the level of corruption. The multidimensional regression model has confirmed the positive effect of electronization. However, the most significant effect on the level of corruption in the country had the performance of the economy in the examined period and selected set of countries.
Electronization of public administration as a tool for the corruption reduction
Keywords: corruption; electronization; bag plots; regression analysis; CPI; EGDI; D73; E 6; H11